2014
DOI: 10.17821/srels/2014/v51i6/56912
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Awareness and Preparedness in Nigerian Polytechenic Libraries: A Survey

Abstract: The paper examined the disaster awareness and preparedness in Nigerian polytechnic libraries. A survey research design was used for the study. Purposive sampling was used to select one hundred and forty respondents from the library staff which include the academic staff and the non-academic staff. Questionnaire was used as the main instrument for gathering data. Findings revealed that that there is no disaster control plans in the polytechnic libraries under the study and the staff admitted that they were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This is reflected by Jaeger et al (2006) who found that the most important service of libraries provided during crisis is the provision of internet access for information sharing. Owolabi et al (2014) suggested that crisis control programs should be considered obligatory in all polytechnic libraries as part of their agenda.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is reflected by Jaeger et al (2006) who found that the most important service of libraries provided during crisis is the provision of internet access for information sharing. Owolabi et al (2014) suggested that crisis control programs should be considered obligatory in all polytechnic libraries as part of their agenda.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies which point to an important role for libraries in sharing information about the crisis on the websites, cooperating with other institutions to provide information, identifying budget constraints, and highlighting gaps in planning. Further, there is an emphasis in several studies on the importance of a written strategic plan of preparedness against disasters, enabling preventive and protective measures, and practical instructions for disaster control and prevention (Aziagba and Edet, 2008; Buchanan, 1998; Kaur, 2009; Owolabi et al, 2014; Rattan, 2013). Likewise, Alajmi (2016) highlighted the issues related to preparedness for crisis management and the resources required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also observed lack of basic disaster management facilities in University of Calabar, Cross River State of Nigeria Choji (2014). repoted that there were inadeqaute major disaster management facilities in academic libraries in Plateau State Owolabi, Lawal, Olukayode, Pelemo & Odenigbo (2014). study discovered that many libraries in Nigeria do not have disaster facilities and common facilities readily available in major libraries in Nigeria were fire extinguishers Issa, Aliyu, Adedeji, Akangbe (2012).…”
mentioning
confidence: 99%